Dual and targeted photodynamic therapy ablation of bacterial and cancer cells using phthalocyanines and porphyrins in the presence of carbon-based nanomaterials - Openda, Yolande Ikala (Rhodes University, Faculty of Science, Department of Chemistry)
Phthalocyanines (Pcs) and porphyrins bearing substituents that possess antibacterial/anticancer properties are used as photosensitizers (PS) for the first time in the work. For targeting specificity and improved photoactivity, the PSs were afterward functionalized with carbon nanomaterials such as graphene quantum dots (GQDs) and detonation nanodiamonds (DNDs) via covalent conjugation (amide or ester bonds) or by non-covalent conjugation (Ï€-Ï€ stacking and electrostatic interactions). Furthermore, the PSs-DNDs nanoconjugates were conjugated to either chitosan-capped silver nanoparticles (CSAg) via amide bonds or to the bare silver nanoparticles (Ag NPs) using the silver- nitrogen affinity. The as-synthesized nanoconjugates were also fully characterized by spectroscopic and microscopic methods together with thermal analysis. The potential photocytotoxicity of the complexes alone and their nanoconjugates against S. aureus and/or E. coli planktonic and biofilm cultures has been evaluated in vitro. Compared to the non- quaternized PSs, the cationic analogs exhibited a higher photodynamic inactivation against the planktonic cells with log10 reduction values above 9 in the viable count using a concentration of ca. 1.25 Î¼M following 30 min exposure to light (Light dose: 943 J/cm2 for Pcs and 250 mW/cm2 for porphyrins). Whereas, at a concentration of ca. 100 Î¼M the cationic PSs showed complete eradication of biofilms upon 30 min exposure to light. As a result of conjugation to carbon-based nanomaterials and silver nanoparticles, the compounds proved to be more effective as they exhibited stronger antibacterial and anti-biofilm activities on the multi-drug resistant bacteria strains due to synergetic effect, compared to PSs alone. This suggests that the newly prepared nanohybrids (PS concentration ca. 100 Î¼M) could be used as potential antimicrobial agents in the treatment of biofilm-related infections. The target nanoconjugates showed all the advantages of two different groups existing on a single entity. In light of the potential advantages of combined chemotherapy and photodynamic antimicrobial chemotherapy (PACT), this work reports for the first time the use of PACT-ciprofloxacin (CIP) dual therapy using selected indium quaternized PSs which showed higher photoactivity with complete eradication of both Gram-positive and Gram-negative bacteria biofilms at concentrations of 8 Î¼M of PS versus 2 Î¼g/mL of the antibiotic following 15 min irradiation time (light dose: 471 J/cm2 for Pcs and fluence: 250 mW/cm2 for porphyrins) on S. aureus. Whereas the total killing of E. coli was obtained when combining 8 or 16 Î¼M of PS combined with 4 Î¼g/mL of CIP. The combined treatment resulted in the complete eradication of the matured biofilms with the highest log10 reduction values of 7.05 and 7.20 on S. aureus and E. coli, respectively. Used as a model, positively charged dimethylamino-chalcone Pcs also exhibited interesting photodynamic therapy (PDT) activity against MCF-7 cancer cells giving IC50 values of 17.9 and 7.4 Î¼M, respectively following 15 min irradiation. Additionally, the TD-B3LYP/LanL2DZ calculations were run on the dimethylaminophenyl- porphyrins to compare the singlet excitation energies of quaternized and non-quaternized porphyrins in vacuo. the study shows excellent agreement between time-dependent density- functional theory (TD-DFT) exciting energies and the experimental S1>S0 excitation energies. The small deviation observed between the calculated and experimental spectra arises from the solvent effect. The excitation energies observed in these UV-Vis spectra mostly originated from electron promotion between the highest occupied molecular orbital (HOMO) for the less intense band and the HOMO-1 for the most intense band of the ground states to the lower unoccupied molecular orbital (LUMO) of the excited states.
Keywords: Phthalocyanines; Porphyrins; Active oxygen; Biofilms; Breast Cancer -- Treatment; Nanostructured materials; Combination therapy; Photochemotherapy